2019
DOI: 10.3390/su11195529
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ESGC Indicators on Financial Performance of Listed Travel and Leisure Companies

Abstract: The objective of this work was to research the impact of environmental, social, governance, and controversies (ESGC) indicators on financial performance. We used a sample of financial and nonfinancial business data from international countries for 2017 obtained through the Thomson Reuters environmental, social, and corporate governance (ESG) database. The company participants in the study belong to the tourism sector and are listed on international stock market indices. The methodology used was based on parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 80 publications
(92 reference statements)
1
12
0
Order By: Relevance
“…In general terms, there is a lack of consensus and a disparity in the literature reviewed. The results obtained in our study for multinationals in the pharmaceutical industry have been confirmed by other researchers in various sectors [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 43 , 44 , 45 , 46 ]. Furthermore, El Ghoul et al [ 25 ] found a significant positive influence on financial performance.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In general terms, there is a lack of consensus and a disparity in the literature reviewed. The results obtained in our study for multinationals in the pharmaceutical industry have been confirmed by other researchers in various sectors [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 43 , 44 , 45 , 46 ]. Furthermore, El Ghoul et al [ 25 ] found a significant positive influence on financial performance.…”
Section: Discussionsupporting
confidence: 89%
“…Few studies focus on showing this relationship through joint ESG and financial performance indicators of companies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Only one jointly incorporates the so-called “ESG controversies” indicator (hereinafter, we refer to this as “controversies” for easy reading) [ 26 ], and no study focuses on the pharmaceutical industry sector. The reason why we add the controversies to our analysis is due to their impact on business performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, it seeks efficiency by saving on resources and treating waste, while offering adequate socio‐environmental performance, all of which leads to an increase in its financial performance. (Busch & Friede, 2018; Rodríguez‐Fernández, Sánchez‐Teba, López‐Toro, & Borrego‐Domínguez, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…financial performance (Busch & Friede, 2018;Rodríguez-Fernández, Sánchez-Teba, López-Toro, & Borrego-Domínguez, 2019…”
mentioning
confidence: 99%